Diel Patterns in Marine Microbial Metatranscriptomes Reflect Differences in Community Metabolic Activity Over Depth on the Continental Shelf of the North Atlantic - Zehnpfennig, Jessica R.; Hansel, Colleen M.; Wankel, Scott D.; Sheik, Cody S.; Horton, Dean J.; Lamborg, Carl H.; Learman, Deric R. (Frontiers in Marine Science, 2022)
Microbial community dynamics are influenced not only by biological but also physical and chemical phenomena (e.g., temperature, sunlight, pH, wave energy) that vary on both short and long-time scales. In this study, samples of continental shelf waters of the northwest Atlantic Ocean were periodically collected from pre-sunrise to post-sunset and at multiple depths over summers of 2016 and 2017. Metatranscriptomic analyses revealed expression of photosynthetic genes in surface water samples corresponding to a diel relationship with sunlight. Photosynthetic genes originated from known phototrophs including Aureococcus, Ostreococcous, Synechocococus, and Prochlorococcus. Photosynthetic gene expression occurred pre-sunrise, suggesting the community initiates transcription before sunlight exposure, ostensibly to harvest energy more efficiently when the anticipated increase in light occurs. Transcripts from photoheterotrophic members of the SAR11 clade were also documented in surface samples, with rhodopsin expression being more abundant pre-sunrise and post-sunrise. Conversely, samples taken from the aphotic layer exhibited expression of transcripts related to nitrification that did not vary over the diel cycle. Nitrification gene transcripts, specifically amoA, nirK, hao, and norAB, were taxonomically related to well-known genera of ammonia oxidizers, such as Nitrospira, Candidatus Nitrosomarinus, Nitrosospira, and Nitrosopumilus. Overall, this study documents the role of light (varying with time and depth) in shaping the photosynthetic microbial community activity in the surface ocean, and further demonstrates that this diel regulation of photosynthesis is decoupled from the activity of the nitrifying microbial community in deeper and darker waters.